Factors Affecting the Effectiveness of Accounting Information Systems in Village Credit Institutions Throughout Jembrana Regency - Ni Luh Gede Putri Wulandari; Made Yenni Latrini (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
This study explores the influence of information system quality, information technology sophistication, and personal technical capability on the effectiveness of Accounting Information Systems (AIS) in Village Credit Institutions (LPDs) in Jembrana Regency. The research adopts a quantitative approach, utilizing a survey method. Questionnaires were distributed to 63 employees from 21 LPDs that have already implemented computerized AIS. The study focuses on assessing how these three independent variables contribute to the effectiveness of AIS in the LPDs. Multiple linear regression was employed for data analysis, allowing the researcher to determine the relationship between the independent variables and the effectiveness of AIS. The respondents were selected from LPDs that had successfully integrated technology into their accounting systems. The primary objective was to understand whether system quality, IT sophistication, and personal technical capability played a significant role in improving AIS performance in these institutions. The findings of the study indicate that all three independent variables—system quality, IT sophistication, and personal technical capability—positively influence the effectiveness of AIS. Specifically, high-quality systems, advanced IT infrastructure, and employees with strong technical skills were found to enhance the operational effectiveness of AIS. This underscores the importance of these factors in ensuring the smooth functioning of AIS in LPDs. As such, LPDs are encouraged to invest in improving system quality, upgrading IT systems, and enhancing the technical skills of their staff to optimize AIS performance. Overall, the study contributes to the understanding of how technological factors can be leveraged to improve accounting processes in financial institutions, particularly in rural settings like LPDs in Jembrana Regency.